Pemilihan Supplier Peralatan Kantor Dengan Metode Weighted Product Pada SMK Swasta YAPDI Bandar Pulau - Riki Handoko; Rizaldi Rizaldi; Akmal Nasution (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Selection of suppliers is a strategic activity because suppliers will supply goods that are critical or will be used in the long term, one of which is the SMK Swasta YAPDI Bandar Pulau. The problem experienced by SMK Swasta YAPDI Bandar Pulau is the difficulty of determining which supplier has good performance in terms of quality, price, delivery and service. So that problems arise related to the non-optimal performance of suppliers which results in inaccuracy of goods supplied to schools and frequent delays in delivery of goods. Another problem is the quality of the goods, which also changes every time the shipment changes without a constant stability of the quality of the goods. Errors in supplier selection have an impact on decreasing the productivity of the SMK Swasta YAPDI Bandar Pulau. If the supplier does not meet what is needed by the school, it will result in delays in the process of employee and teacher activities due to the long delivery time. In addition, selecting the right supplier will significantly reduce the cost of purchasing goods/materials and increase the productivity of work activities. Therefore, this decision support system is needed to help make it easier for schools to get the right suppliers, both in terms of quality, price, delivery and service. And can design a decision support system application so that it can be used as a reference in the selection of office equipment suppliers at SMK Swasta YAPDI Bandar Pulau in accordance with predetermined criteria.